Enhanced ultraviolet photoresponse of diamond photodetector using patterned diamond film and two-step growth process. (January 2019) - Liu, Zhangcheng; Zhao, Dan; Ao, Jin-Ping; Wang, Wei; Chang, Xiaohui; Wang, Yanfeng; Fu, Jiao; Wang, Hong-Xing
Abstract: In this study, we report ultraviolet photoresponse enhancement of diamond photodetector by applying patterned diamond film design and two-step growth process. Diamond stripes are fabricated on the surface and interdigitated electrodes are set perpendicular to them. Before second step growth, surface defects induced during etching process affect the responsivity of supra-band gap light. After second step growth, the surface defects are suppressed, then the responsivity of photodetector on diamond strips are larger than that of photodetector on continuous diamond film. The larger responsivity could be attributed to the quasi-one-dimensional carrier transport and large surface to volume ratio. In additionally, a large electrode space is helpful in enhancing ultraviolet photoresponse while suppressing the visible response.